A Framework Proposal for Blockchain-Based Scientific Publishing Using Shared Governance - Mackey, Tim K.; Shah, Neal; Miyachi, Ken; Short, James; Clauson, Kevin (Frontiers in Blockchain, 2019)
Scientific research activity is reaching a staggering growth rate, introducing new and compounding existing challenges regarding the quality of peer-review, rise of predatory journals, and larger issues involving academic integrity and fraud stemming from the increased pressure to publish. Blockchain, a distributed ledger technology, is well-suited to address some of the challenges specific to scientific publishing. Companies including ARTiFACTS, Pluto, Orvium, and ScienceMatters-EUREKA, along with academic researchers, are exploring blockchain-based solutions to facilitate research data provenance and workflows, optimize the peer-review process, introduce better incentives, and even create new research journals and platforms utilizing blockchain. Building upon a review of these efforts, we propose a governance framework for scientific publishing based on a consortium blockchain model to create a more efficient means of navigating the publishing process. At the center of this framework is a model that adopts shared governance and validated inclusion via a Democratic Autonomous Organization (DAO). A DAO is an entity wherein the organizational rules are implemented and executed via smart contracts. The DAO will be comprised of participants of validated individuals and organizations who are publishers, editors, peer-reviewers, and citizen scientists to manage and oversee the framework. The framework also maps specifically to the publication workflow of submitting, handling, peer-review, and final editorial decision-making for scientific manuscripts. The goal of this framework is to increase transparency of scientific publishing, create a “pedigree” of a manuscript’s research life cycle, and democratize the publication process while maintaining the accepted workflow common to scientific publishing by journals.